Colour change in paintings - Clarricoates, Rhiannon; Dowding, Helen; Gent, Alexandra (Archetype Publications, 2016)
Changes in colour may completely alter the way we see a painting. From blue leaves in a still life, to the blue walls in Van Gogh?s bedroom, our perception of a painting can be informed by an understanding of these changes. When conserving paintings our comprehension of these alterations can influence the way we display and restore them. The papers in this volume were presented at the ICON paintings Group conference 'Appearance and Reality: Examining Colour Change in Paintings' with the aim of providing an overview of colour change in paintings, from the work of the old masters to modern and contemporary painters. They also address the aesthetic considerations related to these changes when approaching conservation treatments and how understanding these variations can influence the restoration and presentation of paintings